Clinical implication and management of rectal cancer with clinically suspicious lateral pelvic lymph node metastasis: A radiation oncologist’s perspective - Yoo, Gyu Sang; Park, Hee Chul; Yu, Jeong Il (Frontiers in Oncology, 2022)
Rectal cancer is the eighth most common malignancy worldwide. With the introduction of total mesorectal excision (TME) and neoadjuvant chemoradiation (NCRT), intrapelvic local control has been remarkably improved. However, lateral pelvic recurrence remains problematic, especially in patients with clinically suspicious lateral pelvic lymph node (LPLN). LPLN dissection has been applied for the management of LPLN metastasis, mainly in Japan and other Eastern countries and Japan, while the role of NCRT is more emphasized and LPLN dissection is performed in very limited cases in Western countries. However, the optimal management strategy for patients with rectal cancer with suspicious LPLN metastasis has not been determined. Herein, we review the latest studies on the optimal management of LPLN metastasis to suggest the most appropriate treatment policies according to current evidence, and discuss future research directions.